2022
DOI: 10.1139/apnm-2022-0195
|View full text |Cite
|
Sign up to set email alerts
|

MoveStrong at home: a feasibility study of a model for remote delivery of functional strength and balance training combined with nutrition education for older pre-frail and frail adults

Abstract: Exercise and nutrition interventions are often recommended for frailty; however, effective strategies are required for real-world implementation. Our primary aim was to assess the feasibility and acceptability of telephone and virtual delivery of MoveStrong, an 8-week exercise and nutrition program with a 4-week follow-up for older pre-frail and frail adults. A priori criteria for success included: recruitment (≥25/12 weeks), retention at follow-up (≥80%), and adherence to exercise and nutrition sessions (≥70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Four of the included studies were nutrition care-based interventions, and the interventions in six studies included mixed dietary nutrition and exercise guidance. The detailed characteristics of all included studies [ [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ] are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the included studies were nutrition care-based interventions, and the interventions in six studies included mixed dietary nutrition and exercise guidance. The detailed characteristics of all included studies [ [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ] are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Rattray et al., 2022 [ 42 ] Australia and New Zealand Qualitative study Dietitians from clinical, community, and residential aged-care ( n = 18) Nutrition care Semi-structured interviews Exploring the barriers and enablers to providing coordinated nutrition care to malnourished or frail clients in the community. Wang et al., 2022 [ 43 ] Canada Feasibility study Older pre-frail and frail adults ( n = 28) Nutrition and exercise Semi-structured interviews Reasons for joining, perceived benefits facilitators of and barriers to behaviour maintenance, and suggestions for future studies. Van Dongen et al., 2020 [ 44 ] Netherlands Process evaluation study Community-dwelling older adults (65 years or older, n = 16); Health care professionals ( n = 37) Support intervention including diet counselling and exercise Semi-structured interviews Acceptability and applicability of ProMuscle in Practice interventions in the community.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations